Influência do ambiente aversivo na resposta nociceptiva de ratos : um estudo sobre o papel de receptores opióides e canabinóides - Cornélio, Alianda Maira (Universidade Federal de São Carlos, 2009)
In innate or learned threatening situations, animals display a set of defensive behaviors specie-specific such as autonomic alterations, flight, fight and antinociception. Exposure of mice to open elevated plus-maze (oEPM: four open arms), an aversive situation, elicits antinociception of high magnitude. However, mechanisms involved in this kind of antinociception are not clear yet. This study investigated whether antinociception induced by exposure to an oEPM shows cross-tolerance with morphine (Exp. I and II); is attenuated by repetead exposure to the oEPM (Exp. III); is blocked by systemic treatment with naltrexone (Exp. IV); is prevented by adrenalectomy (Exp. V); persists after animal removal from the oEPM and if there are sex-related differences in this factor (Exp. VI); is mediated by CB1 cannabinoid receptor (Exp. VII). Rats were daily treated with morphine (M, 5 mg/kg, i.p.) or distilled water (DW) for 5 consecutive days (antinociceptive tolerance assessed by the tailflick test). Next day, rats received formalin 2.5% injection (50 μL) into the right hind paw and, after first phase of formalin test, they were treated with M or DW. 25 minutes after formalin injection into the paw, time spent licking the injected paw was recorded for 10 minutes (Exp. 1). Similar procedure was followed in the Experiment II, except that time spent licking the paw was recorded during exposure to the oEPM or enclosed EPM (eEPM: four arms enclosed) in undrugged rats. In Experiment III, nociception was evaluated in rats submitted to 1, 2, 3, 4 or 6 exposures to either eEPM or oEPM (formalin was injected only during the last exposure). Experiment IV investigated the effects of naltrexone (0 and 2.5 mg/kg; s.c.) on nociception during eEPM or oEPM exposure. Nociception was also assessed during the eEPM or oEPM exposure in sham and adrenalectomized rats (exp. V). In experiment VII, rats were treated with vehicle (DMSO 60%) or AM251 (1 mg/kg, i.p., CB1 receptor antagonist). Fifteen minutes later, animals received formalin injection into the paw and, 25 minutes after, they were exposed to the eEPM or oEPM. In experiment VI, male and female rats were exposed to eEPM or oEPM (with no noxious stimulus during exposure) and imediately after they were tested on the hot plate test (52.4 °C). Results showed that antinociception induced by oEPM does not display cross-tolerance to morphine; was not altered for at least 6 exposures to the maze; failed to be reversed by naltrexone; was not prevented by adrenalectomy and was not blocked by AM251. In addition, this antinociception does not persist after animal removal of the apparatus, by contrast, it occurs a hyperalgesia (as assessed by hot plate test), a response that does not depend on sex-related differences. Results suggest that antinociception induced by oEPM: is not mediated by opioid system or CB1 cannabinoid receptors and it is not sensitive to corticosterone. Furthermore, animal removal of aversive environment alters nociceptive response from antinociception to hyperalgesia, a phenomenon that is independent of the gender.
Keywords: Neuropsicofarmacologia; Labirinto em cruz elevado; Ratos; Estresse; Analgesia; Medo; Antinocicepção induzida pelo medo; Opióides; Canabinóides; Hiperalgesia; Teste de formalina; Teste de retirada da cauda. Teste da placa quente; Fear-induced antinociception; Opioid; Cannabinoid; Elevated plus maze; Hyperalgesia; Formalin test; Tail flick test; Hot plate test; CIENCIAS BIOLOGICAS::FISIOLOGIA